PERBEDAAN PENGGUNAAN MEDIA PENDIDIKAN TERHADAP PERUBAHAN PENGETAHUAN DAN SIKAP IBU DALAM SARAPAN ANAK SEKOLAH DASAR DI KABUPATEN BOGOR - Ikeu Ekayanti; Dodik Briawan; Imas Destiara (Jurnal Gizi dan Pangan, 2013)
The objective of the study was to analyze the differences of applying educational media to change mother’s knowledge and attitude on the breakfast of the elementary school children in Bogor District. The study was a quasy experimental study. Subjects in this research were 225 mothers of elementary school children in the nine villages in Bogor District. Nutrition education media used for this study were power point slides, flip charts, and combination of the power point slides and leaflets. Score of knowledge and attitude on breakfast increased significantly after the intervention. ANOVA analysis results on knowledge and attitude on the breakfast showed better improvement for the combination of power point slides and leaflets. The proportion of knowledge and attitude of the mothers increased after the intervention. The combination of the power point slides and leaflets was the type of educational media which could increase the rate of mother’s knowledge and attitude score compared to power point slides and flip chart.